Literature Review: Implementation of PSAK 22 Business Combination Accounting on Financial Performance of Companies in Indonesia - Juana Dewi Maharani; Desy Sarina Br Barutu; Dinda Rinata; M. Irvan Ayang Daharo; Naina Yulia Hafni; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
This article discusses business combinations in accounting referring to PSAK 22 which is now called PSAK 103 regarding business combinations, using a literature review approach. This study assesses the impact of PSAK 22 on the company's financial performance. Before the implementation of PSAK 22, the "pooling of interests" or "purchase method" method was widely used by companies. Although mergers and acquisitions can often improve financial performance, the results vary across industries. This article is intended as a reference for further research on business combinations based on PSAK 22/103 and also the need for more comprehensive case studies and various variables.